Produção de subjetividades no trabalho docente no curso de administração da UFES : um olhar ergológico - Freitas, Vanessa Carla de (2017)
This qualitative study has investigated the production of subjectivity in the teaching work through an ergological look. It has identified the forms of production of subjectivity and the relation between Previous Standards, subjectivities and renormalizat